2014
DOI: 10.1039/c4nr00834k
|View full text |Cite
|
Sign up to set email alerts
|

High-yield synthesis of triangular gold nanoplates with improved shape uniformity, tunable edge length and thickness

Abstract: We report the synthesis of uniform triangular gold nanoplates by a modified seeded growth method. The concentration of cetyltrimethylammonium bromide (CTAB) in the growth solution and the time interval between multiple steps of growth were important factors which determined the formation of uniform triangular Au nanoplates. In addition, by further isotropic overgrowth, the thickness of triangular Au nanoplates can be finely tuned within a wide range of 10-80 nm, which at present remains a challenge using conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 51 publications
3
102
0
Order By: Relevance
“…More information about the effects of nanoparticle size and shape on LSPR sensitivity can be found in the recent reviews [13,71]. [109,112,113,116,123,127,[131][132][133] with permission.…”
Section: Effect Of Nanoparticle Composition Size and Shape On Plasmomentioning
confidence: 98%
“…More information about the effects of nanoparticle size and shape on LSPR sensitivity can be found in the recent reviews [13,71]. [109,112,113,116,123,127,[131][132][133] with permission.…”
Section: Effect Of Nanoparticle Composition Size and Shape On Plasmomentioning
confidence: 98%
“…102 A recent study of seeded growth of Au nanoplates showed that control of edge length and thickness, and simultaneous improvement of the uniformity and yield can be achieved by finely tuning the experimental conditions, such as the time interval between multiple steps of growth and the concentration of CTAB in the solution. 103 In addition to the aforementioned control of size, shape and yield by seeded growth, our group recently discovered that there is a crystal structure change in the synthesis of square-like Au plates from ultrathin AuSSs (Fig. 3A–C).…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…This is significant since reports of synthesis of gold nanotriangles by conventional methods are relatively few. 26 Spherical forms were abundant (Figs. 5(b and e)).…”
Section: Using Extract Of Fresh Flowersmentioning
confidence: 99%